Culture and society in early modern Breifne/Cavan - Scott, Brendan (Four Courts, 2009)
Introduction: continuity and change in Breifne/Cavan / Brendan Scott -- Duanaire Méig Shamhradháin, the MacGovern Poembook: an important Bréifne contribution to Gaelic learning / Nollaig Ó Muráile -- "Wily women of God" in Breifne's late medieval and early modern devotional collections / Salvador Ryan -- The making of O'Rourke, 1536 / Raymond Gillespie -- Elizabethan Cavan: the institutions of Tudor government in an Irish county / Christopher Maginn -- The indigenous and colonial urbanization of Cavan town, c. 1300-c. 1641 / Jonathan Cherry -- Surveying and mapping plantation in Cavan, c. 1580-1622 / Annaleigh Margey -- The Scots in plantation Cavan, 1610-42 / William Roulston -- Catholic revival in Kilmore diocese, 1603-41 / Brian Mac Cuarta -- Venice in Cavan: the career of William Bedell, 1572-1642 / John McCafferty -- Cavan in 1638: natives and newcomers / Clodagh Tait -- Reporting the 1641 rising in Cavan and Leitrim / Brendan Scott